Students’ Perception of Using Kahoot Application by the Second-Year Students of SMA Negeri 2 Tambang - Fitri, Indah Nabila; Erni, Erni; Aruan, Rumiri Rotua (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
Kahoot has become a popular application for language learning nowadays. This research aims to find out how the perceptions of the second-year students of SMA Negeri 2 Tambang by using Kahoot application in learning English. The research sample was taken by using the purposive sampling technique that was from second-year students. The number of sample was 72 students. The data were collected by using a questionnaire. There are a total of 30 questionnaire items. A Likert scale was used in this study using survey design with a quantitative research. There are four choices from strongly agree to strongly disagree without using neutral answers. The research result reveals that the second-year students have the perception in which Kahoot keeps motivated, effective to be used as a test or assessment media, is easy to understand and apply by students in learning English. Rests are unsatisfactory like students still felt tense in doing the questionnaire test because of the the timer feature and it is less easy to access due to poor internet networks. Based on the research result, students are recommended to use Kahoot in learning English in the class because it helps them to build their enthusiasm for learning and understand the material more easily.